2021
DOI: 10.1099/ijsem.0.004577
|View full text |Cite
|
Sign up to set email alerts
|

Winogradskyella endarachnes sp. nov., a marine bacterium isolated from the brown alga Endarachne binghamiae

Abstract: A Gram-negative, aerobic, rod-shaped, non-flagellated and motile by gliding bacterium HL2-2T, was isolated from the surface of the brown alga Endarachne binghamiae in China. The 16S rRNA gene sequence analysis showed that this strain was affiliated with the genus Winogradskyella in the family Flavobacteriaceae and presented great similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Differential of isolate APC 3343 T and closely Winogradskyella type strainsStrains: 1, APC 3343 T (data from this study); 2, W. algae Kr9-9 T (data from Kurilenko et al[9]); 3, W. damuponensis F081-2 T (data from Lee et al[20]); 4, W. eximia KMM 3944 T (data from Nedashkovskaya et al[1] and Nedashkovskaya et al[4]); 5, W. litoriviva KMM 6491 T (data from Nedashkovskaya et al[7]); 6, W. endarachnes HL2-2 T (data from Xu et al[10]). nd, No data available; +, positive; −, negative; w, weakly positive.…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…Differential of isolate APC 3343 T and closely Winogradskyella type strainsStrains: 1, APC 3343 T (data from this study); 2, W. algae Kr9-9 T (data from Kurilenko et al[9]); 3, W. damuponensis F081-2 T (data from Lee et al[20]); 4, W. eximia KMM 3944 T (data from Nedashkovskaya et al[1] and Nedashkovskaya et al[4]); 5, W. litoriviva KMM 6491 T (data from Nedashkovskaya et al[7]); 6, W. endarachnes HL2-2 T (data from Xu et al[10]). nd, No data available; +, positive; −, negative; w, weakly positive.…”
mentioning
confidence: 65%
“…The 16S rRNA gene sequence similarity analysis indicated that APC 3343 T was most closely related to members of the genus Winogradskyella within the family Flavobacteriaceae . The APC 3343 T sequence showed the highest similarity to that of Winogradskyella algae Kr9-9 T [9] (98.46 % similarity), followed by Winogradskyella damuponensis F081-2 T [20] (98.07 %), Winogradskyella eximia CECT 7946 T (=KMM 3944 T ) [1] (97.93 %), Winogradskyella litoriviva KMM 6491 T [7] (97.79 %) and Winogradskyella endarachnes HL2-2 T [10] (97.79 %). These closely related strains were selected to be used as reference strains for the comparative phenotypic, biochemical and chemotaxonomic analyses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expect for JN874375_g as a rarely studied Flavobacteriia, all the remaining Tier-1 members are flagellated and therefore highly motile 45,46 . In comparison, all Tier-2 members lack flagellum but showed gliding or wobbling movements 47,48 , while all Tier-3 members are non-motile 49 . Since the Tiers were sorted by the significance of ecological features, it suggests motility may greatly contribute to earning ecological niches in the phycosphere.…”
Section: Discussionmentioning
confidence: 93%
“…The pigments, capnophilic metabolism, gliding motility and isoprenoid quinone were determined using previously described methods [35]. Cell morphology and motility were observed by transmission electron microscopy (JEM-1230, jeol ) [36]. Carbon source utilization, substrate oxidation, enzyme activities and other characteristics were investigated using Gram-negative MicroPlates (Biolog GENIII), and API ZYM and API 20NE test kits (bioMérieux).…”
Section: Methodsmentioning
confidence: 99%